Instrument to Measure Psychological Contract Violation in Pharmacy Students - Spies, Alan R. (American Journal of Pharmaceutical Education, 2010)
OBJECTIVES: To adapt and evaluate an instrument that measures perceived psychological contract violations in pharmacy students by schools and colleges of pharmacy. DESIGN: A psychological contract violations measure was developed from existing literature and the 1997 ACPE Guidelines and pilot-tested with second-year pharmacy students at 2 schools of pharmacy. A revised measure then was administered to second-year pharmacy students at 6 schools of pharmacy. Using a 5-point Likert-type scale, participants were asked to indicate the level of obligations they received compared to what was promised by the school of pharmacy. RESULTS: Exploratory factor analysis on the psychological contract violations measure was conducted using principal components analysis resulting in 7 factors, which led to a revised measure with 26 items. Using a sample of 339 students, the proposed 7-factor measurement model was tested using confirmatory factor analysis. In general, the results supported the hypothesized model. The final 23-item scale demonstrated both reliability and validity. Some students perceived certain aspects of the psychological contract that exists with their school of pharmacy were being violated. CONCLUSION: The psychological contract violations measure may serve as a valuable tool in helping to identify areas where their students believe that schools/colleges of pharmacy have not fulfilled promised obligations.